Pengaruh Minat dan Motivasi Dalam Pembelajaran Pendidikan Jasmani - Muhammad Akbar Syafruddin; Agus Sutriawan; Muflih Wahid Hamid (Phsyical Education Health and Recreation Department of STKIP-YPUP Makassar, 2021)
This research is an experimental research. Overall, the treatment was given for 6 (six) meetings. The material applied is the even semester physical education learning material. Before carrying out the learning process, an initial test is carried out, namely a test of interest and motivation to determine the interest and motivation of students in taking Physical Education lessons. This research was conducted at SMK Negeri 3 Gowa Regency. The conclusions in this study are 1) Interest has a significant contribution to the learning outcomes of physical education; 2) Motivation has a significant contribution to the learning outcomes of physical education.